PENERAPAN MODEL PROJECT-BASED LEARNING TERHADAP EKOLITERASI SISWA KELAS V SDN PARAKANMUNCANG II PADA MATERI EKOSISTEM - Robiah, Bibih Siti; Jayadinata, Asep Kurnia; Maulana, Maulana (Jurnal Pena Ilmiah, 2019)
This research motivated by the increasing levels of the ecological crisis is happening on earth. Requires awareness of humans as intelligent beings who inhabit the earth to overcome it. The purpose of this study was to determine the difference ekoliterasi students using a model project-based learning with conventional learning. Methods and research design used in this research is quasi experiment with nonequivalent control group design. Samples were taken from class II SDN Parakanmuncang VB as an experimental class and class VC as the control class. The results of this study, is a positive influence that showed an increase ekoliterasi students in the experimental class and control class and the use of model of project-based learning is more effective in improving student ekoliterasi significantly than expository.